IMPROVING THE ABILITY TO STORY OF EXPERIENCES USING COMMUNICATION TECHNOLOGY IN IPS LESSONS THROUGH IMAGE MEDIA FOR CLASS IV TUNAGRAHITA SLB KEMBAR KARYA DEVELOPMENT III CITY OF BEKASI - Siti Yuliyanah (International Journal Labs, 2022)
Improve students' ability to increase interest in learning about describing the development of communication technology with image media in class IV/C SLB KKIII Bekasi City. Professional Ability Consolidation Report (PKP) The purpose of this study is to increase student learning about describing the development of communication technology with image media in class IV SLB KK III Bekasi. It was held at SLB KK III Bekasi, Kayuringin District. This study used the CAR research method and was carried out in 2 cycles, consisting of four stages, namely planning, implementation, observation, and reflection. The results of this study can improve the teaching and learning process in class IV mentally retarded especially in Social Sciences (IPS). Therefore, it is necessary to develop learning theory, especially with the development of science in various fields and various new guidelines for the quality of the process and results of learning. Conclusion 1) In presenting the material it will be easier for students to accept by using the question and answer method. 2) Giving examples of communication technology through visual aids makes it easier for students to understand the material. 3) Students will easily understand the material if given a lot of practice and guidance.